PENGAWASAN USAHA WARUNG INTERNET KOTA PEKANBARU - Lia Susanti; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The number of Internet Cafes in Pekanbaru City is the highest number compared to the City / Regency in Riau Province. Based on the observations that the authors do in the field, it is seen that many internet cafes in Pekanbaru City violate regulations such as its many internet cafes that operate beyond the operational hours, many students who play in internet cafes at study hours. based on the above, the researcher is interested to study how the Internet Cafes Supervision in Pekanbaru City. This type of research is done by qualitative approach with descriptive method. Based on field facts with observation data collection techniques, interviews, and documentation. The concept of Theory used is Supervision according to Sukanto that there are 3 variables are: Determining the standard of supervision, Conduct research on the object of supervision, Make corrective action against violations. The informant of this research is from Satpol Police Unit of Pekanbaru City. The results of research conducted by researchers can be concluded that the supervision of internet cafes business in Pekanbaru City has been running of internet cafes business in Pekanbaru City. Factors influencing the supervision of internet kiosk business Pekanbaru is the lack of personnel of Pekanbaru Police Precinct Police Unit in conducting supervision, because the number of supervisors with the supervised is not worth it, then the second factor is the supervision system which is not good supervision system, that is supervision rarely done and not routine then still often the occurrence of leaked information raids to internet cafe business owners at the time will be done raids. Keywords: Internet Cafes, Operations, Monitoring